The impact of macroeconomic variables on stock market performance in sri lanka - Nanayakkara, M.S.; Darshi, G.A.N. (University of Jaffna, 2016)
The stock market is one of the major pillars of long term economic growth in any nd country. As an emerging stock market, Colombo Stock Exchange (CSE) has reached World 2 best performing stock market in 2010. With the end of civil war lots of local and foreign investors were attracted to the Sri Lankan stock market and other factors also changed rapidly during that period. Due to prevailed favorable economic and political condition in Sri Lanka, it can be seen the boom which creates a market bubble until mid-2011. After mid 2011, Sri Lankan stock market has not reported significance performance and the determinants of stock market performance remain unclear. It is generally apparent that macroeconomic variables have a significant role in the overall performance of the stock market. Therefore, investigation of the variables which affect the stock market performance is an important empirical study since Sri Lankan stock market has many ups and downs during the past years. This paper is to examine the impact of macroeconomic variables on stock market performance in CSE in Sri Lanka based on time series data from2004 to 2014.The Linear Regression analysis was applied to examine the impact of macroeconomic variables on All Share Price Index (ASPI). It reveals that selected macroeconomic variables have a high explanatory power in explaining stock market performance. Further, it is found that Interest Rate (IR), Exchange Rate (ER), Inflation Rate (IFR) and Fiscal Deficit (FD) have a negative impact on ASPI. In addition, Gross Domestic Product (GDP) and Treasury Bill Interest Rate (TBI) are positively related to ASPI. Moreover, the findings reveal that GDP is the most significant variable in affecting stock market performance in Sri Lanka.
Keywords: Colombo stock exchange; Macroeconomic determinants; Sri lanka; Stock market performance